Dear Diego - Poniatowska, Elena (Aris & Phillips Hispanic classics., 2012)
When Diego Rivera's biographer, Bertram Wolfe, was sifting though the painter's jumbled collection of correspondence, he encountered a series of Parisian letters from Angelina Beloff. Long before Diego had become famous for his Mexican murals or applauded for his renowned wife, Frida Kahlo, Angelina had been his wife for over ten years while the young Rivera had lived as a poor and obscure artist in the city of light. Wolfe was impressed by the letters Beloff wrote to her husband after his definitive departure for Mexico and included a chapter on them and the Russian painter in his biography of the muralist. Several years later, Mexican author Elena Poniatowska read Wolfe's biography and, deeply impressed by Angelina Beloff's letters, decided to rewrite them. The result is Querido Diego, te abraza Quiela, a masterful blending of fact and fiction that creates a novella out of twelve imagined letters that Quiela (Angelina) writes to Diego over a nine-month period. Within them, we are able to view the artist's world of post-war Paris where Quiela struggles forward without her husband while falling back onto fond memories of their time spent together as well as suffering the torment of darker moments she also lived with the painter. It offers the reader a beautiful portrait of life and art in an iconic city towards the beginning of the 20th century. This brief work exhibits some of the fundamental traits encountered in Poniatowska's narratives: a focus on strong women, an interest in the real and the marginal and a love for Mexico. While translations of this narrative do exist in various languages, Nathanial Gardner's bilingual edition is a new initiative that introduces the reader to the work of one of Mexico's most celebrated female writers and assists the student and enthusiast understand this author's place and importance in Latin American letters. Elena Poniatowska was been awarded the prestigious Premio Cervantes (Cervantes Prize) on 23rd of April2014, the anniversary of the death of Miguel de Cervantes.